2022-RA-1099-ESGO Impact of age on surgical resection margins of vulvar squamous cell carcinoma: multicenter descriptive study. (20th October 2022) - Raimond, Emilie; Ambroise, Caroline; Mimoun, Camille; Kerbage, Yohan; Ouldamer, Lobna; Bendifallah, Sofiane; Carcopino, Xavier; Koskas, Martin; Bolze, Pierre adrien; Vincent, Lavoue; Gauthier, Tristan; Fauconnier, Arnaud; et al.
Abstract : Introduction/Background: Vulvar cancer is a rare cancer that most often affects elderly women and is therefore vulnerable. The first-line treatment for vulvar cancer is surgery. Histological resection margins ≥ 8 mm are recommended. The aim of this study was to assess the impact of patient age on the size of surgical resection margins for vulvar cancer. Methodology: This is a multicenter retrospective observational study of 596 cases of vulvar squamous cell carcinoma. An age limit of 65 years was chosen to define the 2 groups of patients to be compared. Results: Patients < 65 years old presented clinically smaller tumors than older patients. Surgically, more patients benefited from total radical vulvectomy in the group ≥ 65 years (28.2% (n=107) versus 20.3% (n=44), p=0.04). The mean postoperative lesion size was 29.3 mm (2–120) in the group < 65 years old versus 32.3 mm (1–150) in the group ≥ 65 years old (p = 0.044). The proportion of excision in sano was similar and there was no difference in obtaining margins > 8 mm between the 2 groups. However, more patients required revision surgery in the group < 65 years. Conclusion: Despite a larger tumor size depending on the age of the patients, age is not a factor influencing the obtaining of resection margins > 8 mm.